Effect of carbon dioxide content in biogas on turbulent combustion in the combustor of micro gas turbine. (March 2020) - Liu, Hongzhao; Wang, Yuzhang; Yu, Tao; Liu, Hecong; Cai, Weiwei; Weng, Shilie
Abstract: China has huge potential on biogas resources and the distributed energy system (DES) based on micro gas turbine provides an effective way for biogas utilization. In this work, turbulent combustion characteristics in the combustor of micro gas turbine for DES were numerically and experimentally studied, and the effect of carbon dioxide content in biogas on the turbulent flame was mainly analyzed. Turbulent flames structures of natural gas and three kinds of biogas under various equivalence ratios were measured by three-dimensional (3D) combustion diagnostic technique based on computed tomography of chemiluminescence (CTC). The results show that the carbon dioxide content in the fuel has a great influence on flame structure of turbulent combustion. The increase of carbon dioxide content in the fuel not only reduces turbulent combustion rate, but also makes the combustion stability worse. With the decrease of equivalence ratio, the effect becomes greater. With the increase of carbon dioxide volume fraction, combustion flame is gradually away from the outlet of the nozzle. When volume fraction of carbon dioxide is 50%, the distance between the combustion flame and the nozzle outlet increases the 100 mm. Furthermore, carbon dioxide weakens the effect of excess air on the CH* distribution and turbulent flame. Highlights: Dynamic process and 3D reconstruction of turbulent flame are obtained. Content of carbon dioxide has a great influence on the flame structure. CO2 weakens the effect of excess air on the CH* distribution of turbulent flame. CO2 in biogas enhances the instability of turbulent combustion.